Effect of Macroeconomic Indicators on Agricultural Output in Nigeria (Global Journal of Management and Business Research, 2019)
This study investigated the effect of macroeconomics indicators' dynamics on agricultural output in Nigeria. The study modeled exchange rate, interest rate, money supply and inflation volatility, against agricultural output using quarterly time series data for the period 1981:1 to 2018:4 (from various publications of the Central Bank of Nigeria Statistical Bulletin and National Bureau of Statistics). The data were analysed using descriptive and econometrics techniques. The volatility series of inflation was generated by employing the standard deviation while the level of volatility was established by employing the Generalized Autoregressive Conditional Heteroscedasticity (GARCH) technique. The regression model was estimated with the fully modified ordinary least square (FMOLS) estimation method to capture the effect of the macroeconomic indicators on agricultural output. The trend analysis showed that both inflation rate and agricultural output were unstable for the period under study. The results show that inflation rate in Nigeria is volatile over the period of study and inflation volatility has a negative but significant impact on agricultural growth. Exchange rate and cost of fund also possess varying impacts on agricultural output and therefore, the study recommends that moderate expansionary monetary policy measures that is guided by stable exchange rate environment is appropriate to curtail the dynamics of inflation rate and its derogatory impact on agricultural output in Nigeria.
Keywords: exchange rate; interest rate; money supply; inflation volatility; agricultural output; Nigeria